Characterization of the novel HLA‐A*02:944 allele by sequencing‐based typing. (12th November 2020) - Cargou, Marine; Elsermans, Vincent; Top, Isabelle; Guidicelli, Gwendaline; Visentin, Jonathan
Abstract : HLA‐A*02:944 differs from HLA‐A*02:01:01:01 by one nucleotide substitution in Codon 114 in Exon 3.